--- a/src/HOL/ROOT Sat Dec 27 20:32:06 2014 +0100
+++ b/src/HOL/ROOT Sun Dec 28 15:42:34 2014 +1100
@@ -559,6 +559,8 @@
PER
NatSum
ThreeDivides
+ Cubic_Quartic
+ Pythagoras
Intuitionistic
CTL
Arith_Examples
--- /dev/null Thu Jan 01 00:00:00 1970 +0000
+++ b/src/HOL/ex/Cubic_Quartic.thy Sun Dec 28 15:42:34 2014 +1100
@@ -0,0 +1,145 @@
+(* Title: HOL/ex/Cubic_Quartic.thy
+ Author: Amine Chaieb
+*)
+
+header "The Cubic and Quartic Root Formulas"
+
+theory Cubic_Quartic
+imports Complex_Main
+begin
+
+section "The Cubic Formula"
+
+definition "ccbrt z = (SOME (w::complex). w^3 = z)"
+
+lemma ccbrt: "(ccbrt z) ^ 3 = z"
+proof-
+ from rcis_Ex obtain r a where ra: "z = rcis r a" by blast
+ let ?r' = "if r < 0 then - root 3 (-r) else root 3 r"
+ let ?a' = "a/3"
+ have "rcis ?r' ?a' ^ 3 = rcis r a" by (cases "r<0", simp_all add: DeMoivre2)
+ hence th: "\<exists>w. w^3 = z" unfolding ra by blast
+ from someI_ex[OF th] show ?thesis unfolding ccbrt_def by blast
+qed
+
+text "The reduction to a simpler form:"
+
+lemma cubic_reduction:
+ fixes a :: complex
+ assumes H: "a \<noteq> 0 \<and> x = y - b / (3 * a) \<and> p = (3* a * c - b^2) / (9 * a^2) \<and>
+ q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3)"
+ shows "a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow> y^3 + 3 * p * y - 2 * q = 0"
+proof-
+ from H have "3*a \<noteq> 0" "9*a^2 \<noteq> 0" "54*a^3 \<noteq> 0" by auto
+ hence th: "x = y - b / (3 * a) \<longleftrightarrow> (3*a) * x = (3*a) * y - b"
+ "p = (3* a * c - b^2) / (9 * a^2) \<longleftrightarrow> (9 * a^2) * p = (3* a * c - b^2)"
+ "q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3) \<longleftrightarrow>
+ (54 * a^3) * q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d)"
+ by (simp_all add: field_simps)
+ from H[unfolded th] show ?thesis by algebra
+qed
+
+text "The solutions of the special form:"
+
+lemma cubic_basic:
+ fixes s :: complex
+ assumes H: "s^2 = q^2 + p^3 \<and>
+ s1^3 = (if p = 0 then 2 * q else q + s) \<and>
+ s2 = -s1 * (1 + i * t) / 2 \<and>
+ s3 = -s1 * (1 - i * t) / 2 \<and>
+ i^2 + 1 = 0 \<and>
+ t^2 = 3"
+ shows
+ "if p = 0
+ then y^3 + 3 * p * y - 2 * q = 0 \<longleftrightarrow> y = s1 \<or> y = s2 \<or> y = s3
+ else s1 \<noteq> 0 \<and>
+ (y^3 + 3 * p * y - 2 * q = 0 \<longleftrightarrow> (y = s1 - p / s1 \<or> y = s2 - p / s2 \<or> y = s3 - p / s3))"
+proof-
+ { assume p0: "p = 0"
+ with H have ?thesis by (simp add: field_simps) algebra
+ }
+ moreover
+ { assume p0: "p \<noteq> 0"
+ with H have th1: "s1 \<noteq> 0" by (simp add: field_simps) algebra
+ from p0 H th1 have th0: "s2 \<noteq> 0" "s3 \<noteq>0"
+ by (simp_all add: field_simps) algebra+
+ from th1 th0
+ have th: "y = s1 - p / s1 \<longleftrightarrow> s1*y = s1^2 - p"
+ "y = s2 - p / s2 \<longleftrightarrow> s2*y = s2^2 - p"
+ "y = s3 - p / s3 \<longleftrightarrow> s3*y = s3^2 - p"
+ by (simp_all add: field_simps power2_eq_square)
+ from p0 H have ?thesis unfolding th by (simp add: field_simps) algebra
+ }
+ ultimately show ?thesis by blast
+qed
+
+text "Explicit formula for the roots:"
+
+lemma cubic:
+ assumes a0: "a \<noteq> 0"
+ shows "
+ let p = (3 * a * c - b^2) / (9 * a^2) ;
+ q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3);
+ s = csqrt(q^2 + p^3);
+ s1 = (if p = 0 then ccbrt(2 * q) else ccbrt(q + s));
+ s2 = -s1 * (1 + ii * csqrt 3) / 2;
+ s3 = -s1 * (1 - ii * csqrt 3) / 2
+ in if p = 0 then
+ a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow>
+ x = s1 - b / (3 * a) \<or>
+ x = s2 - b / (3 * a) \<or>
+ x = s3 - b / (3 * a)
+ else
+ s1 \<noteq> 0 \<and>
+ (a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow>
+ x = s1 - p / s1 - b / (3 * a) \<or>
+ x = s2 - p / s2 - b / (3 * a) \<or>
+ x = s3 - p / s3 - b / (3 * a))"
+proof-
+ let ?p = "(3 * a * c - b^2) / (9 * a^2)"
+ let ?q = "(9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3)"
+ let ?s = "csqrt(?q^2 + ?p^3)"
+ let ?s1 = "if ?p = 0 then ccbrt(2 * ?q) else ccbrt(?q + ?s)"
+ let ?s2 = "- ?s1 * (1 + ii * csqrt 3) / 2"
+ let ?s3 = "- ?s1 * (1 - ii * csqrt 3) / 2"
+ let ?y = "x + b / (3 * a)"
+ from a0 have zero: "9 * a^2 \<noteq> 0" "a^3 * 54 \<noteq> 0" "(a*3)\<noteq> 0" by auto
+ have eq:"a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow> ?y^3 + 3 * ?p * ?y - 2 * ?q = 0"
+ by (rule cubic_reduction) (auto simp add: field_simps zero a0)
+ have "csqrt 3^2 = 3" by (rule power2_csqrt)
+ hence th0: "?s^2 = ?q^2 + ?p ^ 3 \<and> ?s1^ 3 = (if ?p = 0 then 2 * ?q else ?q + ?s) \<and>
+ ?s2 = - ?s1 * (1 + ii * csqrt 3) / 2 \<and>
+ ?s3 = - ?s1 * (1 - ii * csqrt 3) / 2 \<and>
+ ii^2 + 1 = 0 \<and> csqrt 3^2 = 3"
+ using zero by (simp add: field_simps power2_csqrt ccbrt)
+ from cubic_basic[OF th0, of ?y]
+ show ?thesis
+ apply (simp only: Let_def eq)
+ using zero apply (simp add: field_simps ccbrt power2_csqrt)
+ using zero
+ apply (cases "a * (c * 3) = b^2", simp_all add: field_simps)
+ done
+qed
+
+
+section "The Quartic Formula"
+
+lemma quartic:
+ "(y::real)^3 - b * y^2 + (a * c - 4 * d) * y - a^2 * d + 4 * b * d - c^2 = 0 \<and>
+ R^2 = a^2 / 4 - b + y \<and>
+ s^2 = y^2 - 4 * d \<and>
+ (D^2 = (if R = 0 then 3 * a^2 / 4 - 2 * b + 2 * s
+ else 3 * a^2 / 4 - R^2 - 2 * b + (4 * a * b - 8 * c - a^3) / (4 * R))) \<and>
+ (E^2 = (if R = 0 then 3 * a^2 / 4 - 2 * b - 2 * s
+ else 3 * a^2 / 4 - R^2 - 2 * b - (4 * a * b - 8 * c - a^3) / (4 * R)))
+ \<Longrightarrow> x^4 + a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow>
+ x = -a / 4 + R / 2 + D / 2 \<or>
+ x = -a / 4 + R / 2 - D / 2 \<or>
+ x = -a / 4 - R / 2 + E / 2 \<or>
+ x = -a / 4 - R / 2 - E / 2"
+apply (cases "R=0", simp_all add: field_simps divide_minus_left[symmetric] del: divide_minus_left)
+ apply algebra
+apply algebra
+done
+
+end
\ No newline at end of file
--- /dev/null Thu Jan 01 00:00:00 1970 +0000
+++ b/src/HOL/ex/Pythagoras.thy Sun Dec 28 15:42:34 2014 +1100
@@ -0,0 +1,32 @@
+(* Title: HOL/ex/Pythagoras.thy
+ Author: Amine Chaieb
+*)
+
+header "The Pythagorean Theorem"
+
+theory Pythagoras
+imports Complex_Main
+begin
+
+text {* Expressed in real numbers: *}
+
+lemma pythagoras_verbose:
+ "((A1::real) - B1) * (C1 - B1) + (A2 - B2) * (C2 - B2) = 0 \<Longrightarrow>
+ (C1 - A1) * (C1 - A1) + (C2 - A2) * (C2 - A2) =
+ ((B1 - A1) * (B1 - A1) + (B2 - A2) * (B2 - A2)) + (C1 - B1) * (C1 - B1) + (C2 - B2) * (C2 - B2)"
+ by algebra
+
+
+text {* Expressed in vectors: *}
+
+type_synonym point = "real \<times> real"
+
+lemma pythagoras:
+ defines ort:"orthogonal \<equiv> (\<lambda>(A::point) B. fst A * fst B + snd A * snd B = 0)"
+ and vc:"vector \<equiv> (\<lambda>(A::point) B. (fst A - fst B, snd A - snd B))"
+ and vcn:"vecsqnorm \<equiv> (\<lambda>A::point. fst A ^ 2 + snd A ^2)"
+ assumes o: "orthogonal (vector A B) (vector C B)"
+ shows "vecsqnorm(vector C A) = vecsqnorm(vector B A) + vecsqnorm(vector C B)"
+ using o unfolding ort vc vcn by (algebra add: fst_conv snd_conv)
+
+ end
\ No newline at end of file